(untitled) (Heritage, 2025)
The paper presents a critical analysis of both the demands and the possibilities for depoliticization of the military. The authors deal with fundamental issues and the theoretical model of civil-military relations and depoliticization of the military, with the aim of pointing out the dynamism of civil-military relations and proving that depoliticization of the army (to the extent possible) is a social process, not a state that is not changeable since it has been reached once. Accepting such an approach to depoliticization of the military could be useful in redesigning national institutions. The starting points in the research were the classic Huntington’s concept of (objective) democratic civilian control of the military and the findings of his renowned critics, above all Janowitz and Finer. Huntington’s concept of military neutrality in politics implies a very strict separation of the civilian and military spheres: military officers must not interfere in politics, and politicians must respect the autonomy of the military profession. But politicians who embraced military reforms on the postulates of Huntington’s concept of objective democratic civilian control of the military had to face a key question: is a rigid separation of the military and politics possible? However, the problem of insatiable political interference in military matters emerged. In the long-term, the depoliticization of the military has proved to be a attention-seeking process focused on the relationship between political power and the autonomy of the military profession.